Watch Repairer, Taxi Driver, Librarian: How threatened are our jobs in the digital age? - Obst, Oliver (Journal of EAHIL, 2016)
For 702 different jobs, the Oxford researchers Frey and Osborne examined the degree of susceptibility to computerisation. With a probability of 65%, the occupation “librarian” was calculated as quite good computerisable (1). How does this translates into the reality of our daily work? Do we now all have to be anxious for our jobs? Fearing that our jobs will get lost? That libraries get extinct?